PENGARUH KARAKTERISTIK PERUSAHAAN DAN CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN SUSTAINABILITY REPORT PADA PERUSAHAAN YANG TERDAFTAR DI INDONESIAN SUSTAINABILITY REPORT AWARD (ISRA) TAHUN 2013-2015 - Arini Hidayati, 13.05.52.0183; Indarti, MG. Kentris (Students' Journal of Accounting and Banking, 2017)
The purpose of this study is to analyzed the effect of the characteristic of the company and corporate governance disclosure to sustainability report. Variable characteristic of the company used in research is profitability, liquidity, and leverage. For corporate governance used in research is audit committee and board of directors. Population of this study were taken from company listed on Indonesian sustainability report award period of 2013-2015. This study uses purposive sampling method and collected 50 data. Data analysis whit test clasic assumption and hypoteses test method used multiple regression. The results of this study indicate that the firm's characteristic factor is profitability has no effect on sustainability report disclosure practices. Liquidity and leverage have a significant effect on the practice of sustainability report disclosure. Audit committee variable has no effect on sustainability report disclosure while board variable has significant effect on sustainability report disclosure.Keywords: Sustainability Report, Profitabillity, Liquidity, Leverage, Audit Committee, Board of Directors